Prognostic Value of Epicardial Adipose Tissue in Heart Failure With Mid‐Range and Preserved Ejection Fraction: A Multicenter Study - Wenxian Wang; Yan Gao; Jian Wang; Congshan Ji; Hui Gu; Xianshun Yuan; Shifeng Yang; Ximing Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Epicardial adipose tissue (EAT) accumulation is thought to play a role in the pathophysiology of heart failure (HF) with mid‐range ejection fraction and HF with preserved ejection fraction, but its effect on outcome is unknown. Methods and Results A total of 692 patients with HF with mid‐range ejection fraction or HF with preserved ejection fraction who underwent cardiovascular magnetic resonance at 2 medical centers in China between October 2016 and October 2022 were included in this study. EAT volume and extracellular volume were calculated using cardiovascular magnetic resonance. The main outcome was the composite of all‐cause mortality and first HF hospitalization. Of 692 participants, 41.3% were women. The mean age, body mass index, left ventricular ejection fraction, and EAT volume were 57.0 years, 27.2 kg/m2, 50.0%, and 67.1 mL/m2, respectively. During a median follow‐up of 34 months, 169 patients (24.4%) died or were hospitalized for HF. EAT volume exhibited a strong unadjusted association with the composite outcome (hazard ratio per 1 mL/m2 [HR], 1.57 [95% CI, 1.40–1.76], P<0.001). After fully adjusting, EAT remained associated with the outcome (HR, 1.62 [95% CI, 1.42–1.86], P<0.001). We constructed a baseline multivariable model including comorbidities, New York Heart Association functional class, extracellular volume, age, body mass index, left ventricular ejection fraction, and N‐terminal pro‐brain natriuretic peptide. Addition of EAT volume to the baseline multivariable model significantly improved model performance (C statistic improvement: 0.711–0.760; P<0.001). Conclusions EAT accumulation is associated with an adverse prognosis in patients with HF with mid‐range ejection fraction and those with HF with preserved ejection fraction. In addition, EAT provides incremental prognostic value beyond left ventricular ejection fraction and New York Heart Association class.